2018
DOI: 10.1055/a-0596-7288
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Brain Targeting of Eugenol-Loaded Surface Modified Nanoparticles Through Intranasal Route in the Treatment of Cerebral Ischemia

Abstract: Intranasal administration of developed CS-coated-EUG-loaded-PCL-NPs enhanced the drug bioavailability in rat brain and thus preparation of Eugenol-NPs may help treat cerebral ischemia effectively. The toxicity studies performed at the end revealed safe nature of optimized nanoformulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 70 publications
2
27
0
Order By: Relevance
“…The reason for this difference was that CB had a lower molecular weight and fewer reactive groups than BSA. However, the sizes of both nanoparticles were less than 200 nm, and the nanoparticles were thus suitable for nose‐to‐brain delivery . To further confirm the formation of CB‐Gd‐Cy5.5 and BSA‐Gd‐Cy5.5 nanoparticles, the particle morphologies were characterized using SEM, AFM, and TEM imaging as shown in Figure b,c,e,f; and Figure S1, Supporting Information, which indicated the presence of spherical aggregates and was consistent with the abovementioned data.…”
Section: Resultssupporting
confidence: 79%
“…The reason for this difference was that CB had a lower molecular weight and fewer reactive groups than BSA. However, the sizes of both nanoparticles were less than 200 nm, and the nanoparticles were thus suitable for nose‐to‐brain delivery . To further confirm the formation of CB‐Gd‐Cy5.5 and BSA‐Gd‐Cy5.5 nanoparticles, the particle morphologies were characterized using SEM, AFM, and TEM imaging as shown in Figure b,c,e,f; and Figure S1, Supporting Information, which indicated the presence of spherical aggregates and was consistent with the abovementioned data.…”
Section: Resultssupporting
confidence: 79%
“…A previous study showed that eugenol could protect against hepatic ischemia-reperfusion injury (Abd El Motteleb et al, 2014). Importantly, studies have suggested that eugenol has beneficial effects on cerebral ischemic injury (Won et al, 1998;Ahmad et al, 2018). In addition, a similar compound methyleugenol was demonstrated to alleviate cerebral ischemic injury via inhibiting oxidative stress, inflammation, and apoptosis (Choi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it was shown that higher cytotoxicity was achieved by the delivery of anti-miR-21 and pemetrexed through a lipid-polymer hybrid NPs. Ahmad et al investigated the beneficial effects of eugenol-encapsulated-CS-coated-PCL NPs for the treatment of cerebral ischemia [130]. It was shown that IN administration of these NPs increases their bioavailability in the rat brain and these NPs may lead to the treatment of cerebral ischemia.…”
Section: Poly (ε-Caprolactone) (Pcl)mentioning
confidence: 99%